INTERNALISASI NILAI-NILAI MODERASI ISLAM MELALUI KEGIATAN KEAGAMAAN (STUDI KASUS DI SMK NU 01 JOGOROTO JOMBANG) - Dewi Yulia Reza Putri Karnadi; IvaInayatul Ilahiyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the relationship between Islamic moderation values ​​and religious activities in schools. Islamic moderation values, including tawasuth (justice), tawazun (balance), tasamuh (tolerance), and i'tidal (fairness), are essential in promoting moderate and tolerant attitudes among students. SMK NU 01 Jogoroto Jombang, a school in Jombang, Indonesia, has implemented various religious activities that incorporate these values, such as congregational prayer, recitation of istighosah, yasin, and tahlil, and regular recitation of sholawat. This study seeks to investigate how these activities can foster Islamic moderation values ​​among students, including their participation in religious lessons, religiosity, and tolerance towards people of different religions. The findings of this study are expected to provide insight into how religious activities can shape students' attitudes and behaviors, and inform policy recommendations to improve Islamic education at SMK NU 01 Jogoroto Jombang.